Designing problems in computerized acoustic analyzers - PAPANIKOLAOU, G.; KOSTEK, B. (Archives of Acoustics, 1991)
An attempt to present considerable development in the domain of computerized acoustic devices is made. The synthesis refers mostly to computer-based acoustic analyzers leading in that domain because of their versatility. The mathematical basis as well as the main test functions are reviewed. Hardware and software assumptions of the most universal computerized equipment are shown. The example of an FFT analyzer realized on the basis of the LabVIEW software package for the Macintosh II computer is presented. Conclusions and index of bibliography are included.